Pelatihan Produksi dan Branding Penjualan Masker Kain di Pesantren Modern Daarul Uluum I Kota Bogor - Perdana Wahyu Santosa; Any Setianingrum; Harry Budiantoro; Kasbuntoro Kasbuntoro; Nurlita Malawat (Jurnal Pengabdian UNDIKMA, 2022)
This community service activity aims to improve sewing skills through training in the production and branding of entrepreneurship-based cloth mask sales for santri and female students at Daarul Uluum I Islamic Boarding School, Bogor City. The methods used to implement this service activity included presentations, practicums, and discussions. The participants of this training were 36 students of the Daarul Uluum I Islamic Boarding School in Bogor City. The result showed that the santri and female students in the Daarul Uluum Modern Islamic Boarding School in Bogor could increase their productivity by using sewing skills to make cloth masks. It can protect themselves from Covid-19 by wearing cloth masks and can increase their income by selling masks producing by themselves either through direct sales or indirect sales.